Comparable outcomes from long and short read random sequencing of total RNA for detection of pathogens in chicken respiratory samples - Butt, Salman L.; Kariithi, Henry M.; Volkening, Jeremy D.; Taylor, Tonya L.; Leyson, Christina; Pantin-Jackwood, Mary; Suarez, David L.; Stanton, James B.; Afonso, Claudio L. (Frontiers in Veterinary Science, 2022)
Co-infections of avian species with different RNA viruses and pathogenic bacteria are often misdiagnosed or incompletely characterized using targeted diagnostic methods, which could affect the accurate management of clinical disease. A non-targeted sequencing approach with rapid and precise characterization of pathogens should help respiratory disease management by providing a comprehensive view of the causes of disease. Long-read portable sequencers have significant potential advantages over established short-read sequencers due to portability, speed, and lower cost. The applicability of short reads random sequencing for direct detection of pathogens in clinical poultry samples has been previously demonstrated. Here we demonstrate the feasibility of long read random sequencing approaches to identify disease agents in clinical samples. Experimental oropharyngeal swab samples (n = 12) from chickens infected with infectious bronchitis virus (IBV), avian influenza virus (AIV) and Mycoplasma synoviae (MS) and field-collected clinical oropharyngeal swab samples (n = 11) from Kenyan live bird markets previously testing positive for Newcastle disease virus (NDV) were randomly sequenced on the MinION platform and results validated by comparing to real time PCR and short read random sequencing in the Illumina MiSeq platform. In the swabs from experimental infections, each of three agents in every qRT-PCR-positive sample (CT range 19-34) was detectable within one hour on the MinION platform, except for IAV one agent in one sample (CT = 36.21). Nine of 12 IBV-positive samples were assigned genotypes within one hour, as were five of 11 AIV-positive samples. MinION relative abundances of the test agent (AIV, IBV and MS) were highly correlated with RT-qPCR Ct values (R range -0.82 to -0.98). In field-collected clinical swab samples, NDV (CT range 12-37) was detected in all eleven samples within one hour of MinION sequencing, with 10 of 11 samples accurately genotyped within one hour. All NDV-positive field samples were found to be co-infected with one or more additional respiratory agents. These results demonstrate that MinION sequencing can provide rapid, and sensitive non-targeted detection and genetic characterization of co-existing respiratory pathogens in clinical samples with similar performance to the Illumina MiSeq.